Urban physical education instructional practices and cultural activities - Clements, Rhonda L. (Human Kinetics, 2012)
Clements (physical education, Manhattenville College) and Rady (kinesiology, William Paterson U.) identify six culturally responsive teaching practices, eight beliefs of effective urban physical education teachers, 18 culturally diverse activities, and 20 physical activities appropriate for urban settings. Each activity describes the origin and purpose of the game, the activity area and equipment needed, a simplified teaching process, and a closure question to ask students after participation.